2010
DOI: 10.1063/1.3358461
|View full text |Cite
|
Sign up to set email alerts
|

Onset of filtration convection in a vibrating medium: The Brinkman model

Abstract: The effect of vibrations on the onset of convection in a horizontal fluid saturated porous layer heated either from below or from above is investigated. Vertical vibrations are considered with arbitrary amplitude and frequency. The Brinkman model of flow through porous media is used to describe the non-Darcian effect and the Oberbeck–Boussinesq approximation is invoked. Both continued fraction and Hill’s infinite determinant methods are used to determine the convective threshold for the stress free and rigid b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 32 publications
2
13
0
Order By: Relevance
“…We now explain this transition in terms of marginal curves. The solution through the Floquet analysis revealed marginal curves in the form of a group of loop shaped branches enclosing the region of instability [9]. The bottommost loop was S for very small ω and the minimum of this loop determined the onset condition.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…We now explain this transition in terms of marginal curves. The solution through the Floquet analysis revealed marginal curves in the form of a group of loop shaped branches enclosing the region of instability [9]. The bottommost loop was S for very small ω and the minimum of this loop determined the onset condition.…”
Section: Resultsmentioning
confidence: 97%
“…Also we fixed Pr = 1, κ = 1 and c = Da = 0.1 corresponding to Brinkman porous medium throughout the study. The expression (16) contains, in particular, the corresponding result of Strong [20] for Da = 0, binary fluid case for the Darcy model and Saravanan and Sivakumar [9] for Ra S = 0, pure fluid case for the Brinkman model.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, for high frequencies, the flow and interface deformation converges toward their free state value. Saravanan and Sivakumar ( 2010) recently studied the effect of vibration with arbitrary amplitude and frequency in a porous horizontal saturated fluid heated from below. They demonstrated that these vibrations can produce stabilization or destabilization in function of the chosen amplitude and frequency.…”
Section: Introductionmentioning
confidence: 99%